Toughened nylon 6 composite material and preparation method thereof
By blending PEBA and Surlyn resins with nylon 6 and efficiently mixing with twin screw extruders, the problem of insufficient toughness of nylon 6 at low temperatures or high loads is solved, and its impact strength and dimensional stability are significantly improved, achieving high-level balance of strength, rigidity and toughness.
Patent Information
- Application Number
- CN202411880475.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-19
AI Technical Summary
Nylon 6 has poor toughness at low temperatures or high loads, low impact strength of notch, and is prone to brittle fracture. At the same time, its hygroscopicity leads to poor dimensional stability of the product.
PEBA and Surlyn resins are blended with nylon 6 and mixed with high strength through a twin screw extruder to form a toughened nylon 6 composite material.
The impact strength, tensile strength and bending strength of nylon 6 composite material are significantly improved, and its toughness and dimensional stability are improved, achieving a high-level balance of strength, rigidity and toughness.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nylon 6 composite materials, and in particular to a toughened nylon 6 composite material and a preparation method thereof. Background Art
[0002] Nylon 6 is the variety with the largest output, the most varieties and the widest application among the five general engineering plastics. Compared with other engineering plastics, it has outstanding advantages such as corrosion resistance, oil resistance, heat resistance and processing fluidity. However, it has poor toughness at low temperature or high load, low notch impact strength, and is prone to brittle fracture at the notch. In addition, nylon 6 has strong hygroscopicity, resulting in poor dimensional stability of its products. Therefore, toughening and modifying nylon 6 to make up for its performance defects is of great significance to expand the application of nylon 6.
[0003] At present, the most commonly used toughening modification method is to blend nylon 6 with plastics such as PP, PE, ABS, PET, PC, POM, PPO, or elastomers such as thermoplastic polyurethane elastomers and EPDM rubber, so that nylon 6 and other materials complement each other's advantages, which can effectively improve the toughness and dimensional stability of nylon 6 and reduce water absorption. However, most elastomers have low polarity, weak interfacial adhesion with matrix materials, and poor compatibility. It is necessary to toughen the elastomer and its GMA / MAH grafted modified graft with PA6. In addition, this type of elastomer itself has a low hardness, so this toughening method will be accompanied by a certain loss of other mechanical properties such as rigidity. The increase in the amount of elastomer toughening agent added will cause a significant decrease in both tensile strength and flexural strength. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings and deficiencies of the above-mentioned prior art and provide a toughened nylon 6 composite material and a preparation method thereof. The nylon 6 composite material obtained by the preparation process of the present invention has high impact strength, tensile strength and flexural strength at the same time, and can solve the problems caused by the performance defects of nylon 6 such as poor toughness, low notch impact strength, and easy brittle fracture at the notch. If the composite material is combined with a fiber-type reinforcement material, it is expected to further expand its application in the field of high-strength and high-toughness structural materials.
[0005] The present invention is achieved through the following technical solutions: A toughened nylon 6 composite material, comprising the following components in parts by weight: Nylon 6 79.9 ~ 89.7; PEBA 5 ~ 10; Surlyn resin 5 ~ 15; Copper antioxidant 0.1 ~ 0.3; The density of nylon 6 is 1.1±0.1 g / cm3 , relative viscosity is 2.80~3.00.
[0006] The density of the PEBA is 1.0±0.1 g / cm 3 , the softening point is 170±10℃, and the melting temperature is around 190~220℃.
[0007] The Surlyn resin is an ionomer prepared using ethylene / methacrylic acid copolymer (EMAA) as a precursor, and has a density of about 0.80-0.98 g / cm 3 , the melt flow rate is 2.0~10.0 g / 10min.
[0008] The antioxidant is an organic copper salt composite heat stabilizer H3336, which has the appearance of light green powder.
[0009] The preparation method of the nylon 6 composite comprises the following steps: S1, premixing: adding nylon 6, PEBA, Surlyn resin and antioxidant to a high-speed mixer in sequence for premixing, the mixing temperature is 20-50° C., the rotation speed is 200-400 rpm, and the mixing time is 3-5 minutes to obtain a premix of nylon 6 composite material; S2, twin-screw extruder mixing and granulation: the premix obtained in step S1 is added to a twin-screw extruder for high-intensity mixing and cold water stranding and pelletizing to obtain the nylon 6 composite material. The specific process conditions are: using a twin-screw extruder with an aspect ratio of 40:1 and a screw diameter of 35 mm for extrusion granulation; the feeder speed is set to 10-50 rpm, the rotor speed is 200-400 rpm; the temperature of each section of the extruder is 200-240°C, and the nylon 6 composite material pellets are obtained.
[0010] S3, the pellets obtained by extrusion granulation are placed in a forced air drying oven at 85-90 °C for 5 hours, and then the pellets are injection molded into standard tensile specimens, bending specimens and notched impact specimens (according to ISO 527-1:2012, ISO178:2001 standards) using an injection molding machine.
[0011] The principle of the present invention is: Surlyn resin, which is based on ethylene / methacrylic acid copolymer, has good flexibility and impact resistance due to its structural characteristics as an ionomer. Its polar ionic structure, coupled with the unneutralized carboxylic acid groups and neutralized carboxylate ions on its molecular chain, can react with the amine groups in PA6 and PEBA, so it has good compatibility with nylon 6. The blend of the two can prepare PA6 / Surlyn alloy with balanced rigidity and toughness.
[0012] PEBA is composed of hard segment polyamide and soft segment polyether, and the hard segment and the soft segment are covalently connected by ester bonds. The molecular weight of the polyether segment is about 400~3000 g / mol, and the molecular weight of the polyamide segment is about 500~5000 g / mol. By controlling the hard segment and the soft segment and their ratio, elastomers with different flexibility and hardness can be obtained without adding any plasticizer. PEBA elastomer has both the stiffness of polyamide and the flexibility and elasticity of polyether, which is beneficial to increase the toughness of nylon 6 composite materials. In addition, there are a large number of amide repeating segments on its macromolecular chain, which has a certain compatibility with nylon 6.
[0013] The twin-screw extruder with high-efficiency mixing effect can promote the dispersion of Surlyn resin in the copolymer of nylon 6 and polyether block amide under the action of the copolymer reaction product of Surlyn resin-nylon 6 and Surlyn resin-polyether block amide with volume-increasing effect, which can ensure that the composite material has higher toughness and can achieve a high-level balance of its strength, rigidity and toughness. If the composite material is combined with fiber-type reinforcement materials, it is expected to further expand its application in the field of high-strength and high-toughness structural materials.
[0014] Compared with the prior art, the present invention has the following advantages and effects: (1) PEBA elastomer has both the stiffness of polyamide and the flexibility and elasticity of polyether, which is beneficial to increase the toughness of nylon 6 composite materials. In addition, there are a large number of amide repeating segments on its macromolecular chain, which has a certain compatibility with nylon 6; (2) Surlyn resin, which is based on ethylene / methacrylic acid copolymer, has good flexibility and impact resistance due to its structural characteristics as an ionomer, and its polar ionic structure makes it compatible with the polar nylon 6 matrix, which is expected to expand its application in related fields.
[0015] (3) The twin-screw extruder with high-efficiency mixing effect can promote the dispersion of Surlyn resin in the copolymer of nylon 6 and polyether block amide under the action of the copolymer reaction products of Surlyn resin-nylon 6 and Surlyn resin-polyether block amide with volume-increasing effect, which can ensure that the composite material has higher toughness and can achieve a high-level balance of its strength, rigidity and toughness. If the composite material is combined with fiber-type reinforcement materials, it is expected to further expand its application in the field of high-strength and high-toughness structural materials. DETAILED DESCRIPTION
[0016] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0017] In the embodiment of the present invention, nylon 6 adopts YH800 produced by Hunan Yuehua Chemical Industry Co., Ltd., and its measured density is 1.156 g / cm 3 , the relative viscosity is 2.85±0.03; the copolymer of polyether block amide PEBA adopts the product of Hebei Xuyang Company, and its actual measured density is 1.07 g / cm 3 The softening point is 164°C and the melting temperature is about 208°C; Surlyn resin uses PC2000 from DuPont, USA, with a density of about 0.97g / cm 3 The melt flow rate is 4.5 g / 10min (190℃, 2.16kg); the antioxidant uses the organic copper salt composite heat stabilizer H3336 from Yantai Xintelu New Material Technology Co., Ltd., which has a light green powder appearance.
[0018] The test results of mechanical properties in the embodiments and comparative examples of the present invention are obtained from a universal material testing machine Instron 5965 and a pendulum impact testing machine CEAST 9050. The test results include tensile strength, tensile modulus, flexural strength and notched impact strength.
[0019] Embodiment 1: Weigh each raw material according to the following ratio: 1696 g nylon 6, 200 g PEBA, 100 g Surlyn resin, and 4 g antioxidant. Nylon 6, PEBA, Surlyn resin, and antioxidant were added to a high-speed mixer in sequence for premixing, with a mixing temperature of 40 ° C and a speed of 500 rpm for 3 minutes. Then, the premixed material was added from the feeder to a co-directional parallel twin-screw extruder for melt extrusion granulation. The process conditions were set as follows: screw speed 250 rpm, feeder speed 40 rpm, and extruder section temperature 200-240 ° C. The strands were water-cut and pelletized. The pellets obtained by extrusion granulation were placed in a blast drying oven and dried at 85-90 ° C for 5 hours, and then the pellets were injection molded into standard tensile bars, bending bars, and notched impact bars (according to ISO527-1:2012, ISO 178:2001 standards) using an injection molding machine.
[0020] The specimens were placed in an oven at 80℃ for 4 h before measurement. The tensile, bending and impact tests were performed using the universal material testing machine Instron 5965 and the pendulum impact testing machine CEAST 9050. The tensile test was carried out in accordance with the standard GB / T1040.1-2006, with a tensile rate of 50 mm / min and a span of 64 mm; the bending modulus and bending strength tests were carried out in accordance with the standard GB / T 9341-2008, with a bending rate of 1 mm / min (strain <0.3%) and 10 mm / min (strain > 0.3%), respectively, and a downward deflection of 20 mm; the impact test was carried out in accordance with the standard GB / T 1843-2008, with a pendulum energy of 20 J. The test results are shown in Table 1.
[0021] Embodiment 2: Weigh the raw materials according to the following ratio: 1794 grams of nylon 6, 100 grams of polyether block amide copolymer, 100 grams of Surlyn resin, and 6 grams of antioxidant. Add nylon 6, PEBA, Surlyn resin, aluminum-magnesium hydrotalcite and antioxidant to the high-speed mixer in turn for premixing, with a mixing temperature of 40°C and a speed of 500 rpm for 3 minutes. Then, add the premixed material from the feeder to the co-rotating parallel twin-screw extruder for melt extrusion granulation. The process conditions are set as follows: screw speed 250 rpm, feeder speed 40 rpm, and extruder temperature of each section 200-240°C. The strands are water-cut and pelletized. The pellets obtained by extrusion granulation were placed in a forced air drying oven at 85-90 °C for 5 hours, and then the pellets were injection molded into standard tensile specimens, bending specimens and notched impact specimens (according to ISO527-1:2012, ISO 178:2001 standards) using an injection molding machine.
[0022] The specimens were placed in an oven at 80℃ for 4 h before measurement. The tensile, bending and impact tests were performed using the universal material testing machine Instron 5965 and the pendulum impact testing machine CEAST 9050. The tensile test was carried out in accordance with the standard GB / T1040.1-2006, with a tensile rate of 50 mm / min and a span of 64 mm; the bending modulus and bending strength tests were carried out in accordance with the standard GB / T 9341-2008, with a bending rate of 1 mm / min (strain <0.3%) and 10 mm / min (strain > 0.3%), respectively, and a downward deflection of 20 mm; the impact test was carried out in accordance with the standard GB / T 1843-2008, with a pendulum energy of 20 J. The test results are shown in Table 1.
[0023] Embodiment 3: Weigh each raw material according to the following ratio: 1696 g nylon 6, 100 g PEBA, 200 g Surlyn resin, and 4 g antioxidant. Nylon 6, PEBA, Surlyn resin, and antioxidant were added to a high-speed mixer in sequence for premixing, with a mixing temperature of 40 ° C and a speed of 500 rpm for 3 minutes. Then, the premixed material was added from the feeder to a co-directional parallel twin-screw extruder for melt extrusion granulation. The process conditions were set as follows: screw speed 250 rpm, feeder speed 40 rpm, and extruder section temperature 200-240 ° C. The strands were water-cut and pelletized. The pellets obtained by extrusion granulation were placed in a blast drying oven and dried at 85-90 ° C for 5 hours, and then the pellets were injection molded into standard tensile bars, bending bars, and notched impact bars (according to ISO527-1:2012, ISO 178:2001 standards) using an injection molding machine.
[0024] The specimens were placed in an oven at 80℃ for 4 h before measurement. The tensile, bending and impact tests were performed using the universal material testing machine Instron 5965 and the pendulum impact testing machine CEAST 9050. The tensile test was carried out in accordance with the standard GB / T1040.1-2006, with a tensile rate of 50 mm / min and a span of 64 mm; the bending modulus and bending strength tests were carried out in accordance with the standard GB / T 9341-2008, with a bending rate of 1 mm / min (strain <0.3%) and 10 mm / min (strain > 0.3%), respectively, and a downward deflection of 20 mm; the impact test was carried out in accordance with the standard GB / T 1843-2008, with a pendulum energy of 20 J. The test results are shown in Table 1.
[0025] Embodiment 4: Weigh each raw material according to the following ratio: 1598 g nylon 6, 100 g PEBA, 300 g Surlyn resin, and 2 g antioxidant. Nylon 6, PEBA, Surlyn resin, and antioxidant were added to a high-speed mixer in sequence for premixing, with a mixing temperature of 40 ° C and a speed of 500 rpm for 3 minutes. Then, the premixed material was added from the feeder to a co-directional parallel twin-screw extruder for melt extrusion granulation. The process conditions were set as follows: screw speed 250 rpm, feeder speed 40 rpm, and extruder section temperature 200-240 ° C. The strands were water-cut and pelletized. The pellets obtained by extrusion granulation were placed in a blast drying oven and dried at 85-90 ° C for 5 hours, and then the pellets were injection molded into standard tensile bars, bending bars, and notched impact bars (according to ISO527-1:2012, ISO 178:2001 standards) using an injection molding machine.
[0026] The specimens were placed in an oven at 80℃ for 4 h before measurement. The tensile, bending and impact tests were performed using the universal material testing machine Instron 5965 and the pendulum impact testing machine CEAST 9050. The tensile test was carried out in accordance with the standard GB / T1040.1-2006, with a tensile rate of 50 mm / min and a span of 64 mm; the bending modulus and bending strength tests were carried out in accordance with the standard GB / T 9341-2008, with a bending rate of 1 mm / min (strain <0.3%) and 10 mm / min (strain > 0.3%), respectively, and a downward deflection of 20 mm; the impact test was carried out in accordance with the standard GB / T 1843-2008, with a pendulum energy of 20 J. The test results are shown in Table 1.
[0027] Comparative Example 1: Weigh each raw material according to the following ratio: 1894 g nylon 6, 100 g PEBA, and 6 g antioxidant. Add nylon 6, PEBA, and antioxidant to a high-speed mixer for premixing in sequence, with a mixing temperature of 30 ° C and a speed of 400 rpm for 3 minutes. Then, add the premixed material from the feeder to a co-directional parallel twin-screw extruder for melt extrusion granulation. The process conditions are set as follows: screw speed 200 rpm, feeder speed 30 rpm, and extruder section temperature 200-240 ° C. Stranding water pelletizing. The pellets obtained by extrusion granulation are placed in a blast drying oven and dried at 85-90 ° C for 5 hours, and then the pellets are injection molded into standard tensile bars, bending bars, and notched impact bars (according to ISO527-1:2012, ISO 178:2001 standards) using an injection molding machine.
[0028] The specimens were placed in an oven at 80℃ for 4 h before measurement. The tensile, bending and impact tests were performed using the universal material testing machine Instron 5965 and the pendulum impact testing machine CEAST 9050. The tensile test was carried out in accordance with the standard GB / T1040.1-2006, with a tensile rate of 50 mm / min and a span of 64 mm; the bending modulus and bending strength tests were carried out in accordance with the standard GB / T 9341-2008, with a bending rate of 1 mm / min (strain <0.3%) and 10 mm / min (strain > 0.3%), respectively, and a downward deflection of 20 mm; the impact test was carried out in accordance with the standard GB / T 1843-2008, with a pendulum energy of 20 J. The test results are shown in Table 1.
[0029] Comparative Example 2: Weigh the raw materials according to the following ratio: 1894 g nylon 6, 100 g Surlyn resin, and 6 g antioxidant. Add nylon 6, Surlyn resin, and antioxidant to a high-speed mixer for premixing in sequence, with a mixing temperature of 30°C and a speed of 400 rpm for 3 minutes. Then, add the premixed material from the feeder to a co-rotating parallel twin-screw extruder for melt extrusion granulation. The process conditions are set as follows: screw speed 200 rpm, feeder speed 30 rpm, and extruder section temperature 200-240°C. Strands are water-cut and pelletized. The pellets obtained by extrusion granulation are placed in a blast drying oven and dried at 85-90°C for 5 hours, and then the pellets are injection molded into standard tensile bars, bending bars, and notched impact bars (according to ISO527-1:2012, ISO 178:2001 standards) using an injection molding machine.
[0030] The specimens were placed in an oven at 80℃ for 4 h before measurement. The tensile, bending and impact tests were performed using the universal material testing machine Instron 5965 and the pendulum impact testing machine CEAST 9050. The tensile test was carried out in accordance with the standard GB / T1040.1-2006, with a tensile rate of 50 mm / min and a span of 64 mm; the bending modulus and bending strength tests were carried out in accordance with the standard GB / T 9341-2008, with a bending rate of 1 mm / min (strain <0.3%) and 10 mm / min (strain > 0.3%), respectively, and a downward deflection of 20 mm; the impact test was carried out in accordance with the standard GB / T 1843-2008, with a pendulum energy of 20 J. The test results are shown in Table 1.
[0031] Comparative Example 3: Only nylon 6 was added to the high-speed mixer for pre-mixing (undergoing the same processing process), the mixing temperature was 30°C, the speed was 400 rpm, and the mixing was performed for 3 minutes. Then, the pre-mixed material was added from the feeder to the co-rotating parallel twin-screw extruder for melt extrusion granulation. The process conditions were set as follows: screw speed 200 rpm, feeder speed 30 rpm, and extruder section temperature 200-240°C. The strands were water-cut and pelletized. The pellets obtained by extrusion granulation were placed in a blast drying oven and dried at 85-90°C for 5 hours, and then the pellets were injection molded into standard tensile bars, bending bars and notched impact bars (according to ISO527-1:2012, ISO 178:2001 standards) using an injection molding machine.
[0032] The specimens were placed in an oven at 80℃ for 4 h before measurement. The tensile, bending and impact tests were performed using the universal material testing machine Instron 5965 and the pendulum impact testing machine CEAST 9050. The tensile test was carried out in accordance with the standard GB / T1040.1-2006, with a tensile rate of 50 mm / min and a span of 64 mm; the bending modulus and bending strength tests were carried out in accordance with the standard GB / T 9341-2008, with a bending rate of 1 mm / min (strain <0.3%) and 10 mm / min (strain > 0.3%), respectively, and a downward deflection of 20 mm; the impact test was carried out in accordance with the standard GB / T 1843-2008, with a pendulum energy of 20 J. The test results are shown in Table 1.
[0033] Table 1 Mechanical properties of nylon 6 and composite materials obtained in the examples and comparative examples
[0034] As described above, in order to overcome the problem of poor toughening effect of nylon materials in the prior art, the present invention uses a copolymer of polyether block amide (PEBA) and Surlyn resin to toughen and modify nylon 6.
[0035] PEBA is a type of polyether block amide elastomer that has both the stiffness of polyamide and the flexibility and elasticity of polyether. The amide segments on the molecule make it compatible with nylon 6, and the blending of the two is conducive to increasing the toughness of nylon 6 composite materials. Surlyn resin is a copolymer prepared by free radical polymerization under high temperature and high pressure conditions with ethylene / methacrylic acid copolymer (EMAA) as a precursor. Due to the presence of ionic groups, ionomers can effectively optimize their own physical properties. For example, Surlyn resin has the advantages of both organic acrylic polymers and inorganic ionic compounds, with excellent transparency, low-temperature impact toughness and chemical resistance, and its polar ionic structure makes it compatible with the polar nylon 6 matrix.
[0036] The copolymer of Surlyn resin and polyether block amide with higher toughness has higher toughness than nylon 6. As a blending component, it can effectively toughen nylon 6 while maintaining the high strength and rigidity of the composite material.
[0037] The present invention adopts a twin-screw extruder with a high-efficiency mixing effect. Under the action of the copolymer reaction products of Surlyn resin-nylon 6 and Surlyn resin-polyether block amide with a volume-increasing effect, the dispersion of Surlyn resin in the copolymer of nylon 6 and polyether block amide can be promoted, so that the composite material has higher toughness and can achieve a high-level balance of its strength, rigidity and toughness.
[0038] By mixing selected PEBA and Surlyn resins, the impact strength of nylon 6 composites can be significantly improved, and the toughening modification of nylon 6 can be effectively achieved. At the same time, the tensile and bending properties of the material are also improved to a certain extent, giving the product better mechanical properties. If the composite material is combined with fiber-type reinforcement materials, it is expected to further expand its application in the field of high-strength and high-toughness structural materials.
[0039] The implementation methods of the present invention are not limited to the above-mentioned embodiments, and any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.
Claims
1. A toughened nylon 6 composite material, characterized in that The composition includes the following components in parts by weight: Nylon 6 79.9 ~ 89.7; Polyether block amide copolymer 5 ~ 10; Surlyn resin 5 ~ 15; Copper antioxidant 0.1 ~ 0.
3.
2. The toughened nylon 6 composite material according to claim 1, characterized in that: The nylon 6 has a density of 1.1±0.1 g / cm3 and a relative viscosity of 2.80-3.
00.
3. The toughened nylon 6 composite material according to claim 1, characterized in that: The copolymer of the polyether block amide is a copolymer of caprolactam and tetrahydrofuran, and has a density of 1.0±0.1 g / cm3, a measured softening point of 170±10°C, and a melting temperature of 190-220°C.
4. The toughened nylon 6 composite material according to claim 1, characterized in that: The Surlyn resin is an ionomer prepared from ethylene / methacrylic acid copolymer as a precursor, and has a density of about 0.80-0.95 g / cm 3 , the melt flow rate is 2.0~10.0 g / 10min.
5. The toughened nylon 6 composite material according to claim 1, characterized in that: The antioxidant is an organic copper salt composite heat stabilizer H3336, which has the appearance of light green powder.
6. The method for preparing the toughened nylon 6 composite material according to any one of claims 1 to 5, characterized in that: The steps include: S1, premixing: nylon 6, polyether block amide copolymer, Surlyn resin and antioxidant are sequentially added into a high-speed mixer for premixing, the mixing temperature is 20-50° C., the rotation speed is 100-300 rpm, and the mixing time is 3-5 minutes to obtain a premix of nylon 6 composite material; S2, twin-screw extruder mixing and granulation: the premix obtained in step S1 is added into a twin-screw extruder for high-intensity mixing and cold water stranding and pelletizing to obtain the nylon 6 composite material.
7. The method for preparing the toughened nylon 6 composite material according to claim 6, characterized in that: In step S2, the premix obtained in step S1 is added to a twin-screw extruder for high-intensity mixing and cold water stranding and pelletizing. The specific process conditions are: using a twin-screw extruder with a length-to-diameter ratio of 40:1 and a screw diameter of 35 mm for extrusion granulation; the feeder speed is set to 10-50 rpm, and the twin-screw extruder speed is 200-400 rpm; the temperature of each section of the extruder is 200-240° C., and nylon 6 composite material pellets are obtained.
8. The method for preparing the toughened nylon 6 composite material according to claim 6, characterized in that: The pellets obtained by extrusion granulation in step S2 were placed in a forced air drying oven and dried at 85-90° C. for 5 hours, and then the pellets were injection molded into standard tensile bars, bending bars and notched impact bars using an injection molding machine.
Citation Information
Patent Citations
Polyamide 56 composition with low-temperature toughness and flexural modulus balance
CN109749437A
Toughened biaxially oriented polyamide film and preparation method thereof
CN112480659A
Reinforced biaxially oriented polyamide film as well as preparation method and application thereof
CN113878962A